Visiones contrapuestas sobre las independencias hispanoamericanas: Manuel Abad y Queipo y Manuel Lorenzo de Vidaurre (Tzintzun, Revista de Estudios Históricos, 2019)
The processes of separation of the viceroyalties and captaincies general hispanoamericanos with respect to the Spanish crown provoked a great debate on both sides of the Atlantic, about the nature and perspectives of the links between Spain and its former American possessions, on the causes of the American rebellions , on the course of the civil wars that were fought in the New World, and on the most appropriate measures that should be taken to face them successfully. This article seeks to delve into this debate, through an interesting controversy that took place between 1815 and 1820 and that involved two important and significant figures of the period: the Spaniard based in New Spain Manuel Abad and Queipo and the Peruvian Manuel Lorenzo of Vidaurre.